Kajian Kualitas Air Permukaan di Kabupaten Bojonegoro Menggunakan Pendekatan IKA-NSF - Icha Ayoe Bilbina; Aussie Amalia (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Surface water in Bojonegoro Regency plays a crucial role in meeting domestic, agricultural and ecosystem needs. However, various human activities, such as excessive use of chemical fertilizers in agricultural areas, have led to a decline in water quality. This study analyses the surface water quality using the National Sanitation Foundation Water Quality Index (NSF-WQI) method based on eight parameters: temperature, TDS, pH, DO, BOD, nitrate, phosphate and fecal coliform. The results of the analysis indicate that the surface water quality status falls into the